Pengaruh Orientasi Dan Kompetensi Kewirausahaan Terhadap Kinerja Usahatani Sayuran Di Kabupaten Bogor - Saputra, Redho; Burhanuddin, Burhanuddin; Budi Priatna, Wahyu (Forum Agribisnis, 2025)
Vegetables are an important subsector of horticulture and play a crucial role in agribusiness development in Indonesia. One of the major vegetable production centers is Bogor Regency, West Java. Vegetable production in Bogor Regency from 2016 to 2021 showed a relative increase, despite fluctuations in the harvested area. This increase in production, along with fluctuations in land area, has led to improved productivity. The increase in productivity is believed to be due to farmers’ adoption of entrepreneurial orientation and competence. The objectives of this study were to: 1) analyze the influence of entrepreneurial orientation on farm performance, 2) analyze the influence of entrepreneurial orientation on entrepreneurial competence, 3) analyze the influence of entrepreneurial competence on farm performance, and 4) analyze the mediating effect of entrepreneurial competence on the relationship between entrepreneurial orientation and farm performance. The sampling method used in this study was multistage random sampling, whereas the analysis methods employed included descriptive analysis and PLS-SEM analysis. The results indicate that 1) entrepreneurial orientation has a significant impact on farm performance, 2) entrepreneurial orientation has a significant impact on entrepreneurial competence, 3) entrepreneurial competence has a significant impact on farm performance, and 4) entrepreneurial competence can mediate the relationship between entrepreneurial orientation and farm performance.